FAKTOR â FAKTOR YANG MEMPENGARUHI KINERJA APARAT PEMERINTAH DAERAH KOTA SURABAYA - Wibowo, Anggi Prasetyo; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis researchis aimed to examine the influence of public accountability, budget goal clarity, budgeting preparation participation and decentralization to the performance of local government apparaturs. This research is a quantitative research. The population is the local apparaturs working units (SKPD) in the environment of Surabaya city government. The sample collection technique has been done by using purposive sampling method. The data collection techniques has been done by using survey method. The data is the primary data in the form of questionnaireswhich have been issued to the respondents. The analysis method has been done by using multiple linear regression analysis andthe SPSS (Statistical Product and Services Solutions) 20.0version. The results of the research indicate that public accountability give positive influence to the performance of the local government apparaturs, budget goal clarity give positive influencetothe performance of the local government apparaturs,budget preparation participation has positive influence tothe performance of the local government apparaturs, and decentralization give positive influencetothe performance of the local government apparaturs.Keywords: public accountability, budget goal clarity, budgeting preparation participation, decentralization, local government apparaturs performance.